Thunder Bay : a novel - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery., 2009)
Leaving behind a stressful law enforcement career to become a private investigator in his small Minnesota hometown, Cork O'Connor is asked by an Ojibwe healer to help him find the son the man fathered years earlier, a case that culminates in an attempt on the Ojibwe's life.